A new ICCII based resistor-less current-mode first-order universal filter with electronic tuning capability. (September 2017) - Safari, Leila; Yuce, Erkan; Minaei, Shahram
Abstract: In this paper, a new electronically tunable current-mode (CM) first-order universal filter as a new application for inverting second-generation current conveyors (ICCIIs) is proposed. The proposed circuit is based on two ICCII and a capacitor and does not need any resistors and critical passive component matching conditions. It has one input and multiple outputs and simultaneously realizes both inverting and non-inverting first-order low-pass, high-pass and all-pass responses from the same configuration. Employing ICCII as active building block makes possible using a single transistor in linear region as a variable resistor to control filter properties electronically. Nevertheless, the proposed CM first-order universal filter possesses a floating capacitor which can be easily realized in nowadays integrated circuit technologies. It is designed and simulated with SPICE program using 0.13 µm IBM CMOS parameters and supply voltage of ±0.75 V. Non-ideal analysis and Monte Carlo simulation results are also given, which prove good enough response even in the presence of non-idealities and process parameter variations.